CRIMINAL RESPONSIBILITY OF THE MEMBER OF COUNTERTERRORISM SPECIAL DETACHMENT 88 (DENSUS 88) RELATED TO THE NEGLIGENCE IN HANDLING SUSPECTED TERRORISM WHICH CAUSE CASUALTY - Riefky Rachman Fairuz; Toetik Rahayuningsih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Terrorism is a serious problem throughout countries, no exception in Indonesia. One of the government's efforts in dealing with terrorism is to form a Counterterrorism Special Detachment 88. But in its practice, sometimes the Counterterrorism Special Detachment 88 Members carry out their duty by ignoring the applicable rules. That causes the emergence of casualty, namely one of the suspected terrorist. The incident becomes a polemic in the society related to the criminal responsibility. The research aims to explain the legal basis in every action which taken by the member of Counterterrorism Special Detachment 88 in handling the cases of terrorism criminal acts and explain the criminal responsibility of the member of Counterterrorism Special Detachment 88 due to the negligence in handling suspected terrorist which cause casualty. The researcher used the normative juridical method. Analysis which carried out normatively aimed to support the result of the statement from a thought and/ or asthe answer to the legal problems arising from a case,thus if everything has been resolved then the last stage was the explanation which conducted descriptively. Handling of the suspected terrorism case by the member of Densus 88 that did not comply with the procedures may be subjected to Article 9 of Law Number 48 regarding Judicial Power. Densus 88 member in carrying out their duty which in accordance with the procedure could not be asked forthe responsibility. The negligenceby the member of the Counterterrorism Special Detachment 88 in carrying out their authority was deemed to have violated the code of ethics which needed to be asked for the responsibility.